Phytoremediation of Chromium and some chemical parameters from Tannery effluent by using water Hyacinth (Eichhornia craassipes) (Research in Agriculture Livestock and Fisheries, 2017)
The present study was conducted to explore the efficiency of water hyacinth (Eichhornia crassipes) to cleanup of tannery effluent in terms of pH, TDS, EC, BOD and most importantly Cr. The study period was from November, 2013 to April, 2014. After 7 days of treatment by water hyacinth, the removal rates were: 68.15% for BOD, 59.82% for TDS and 46.56% for EC, where the corresponding rates after 15 days were: 81.73% for BOD, 67.15% for TDS and 61.93% for EC. After treatment with water hyacinth, pH of effluent reached to nearly neutral level from alkaline condition. In this study, major focus was on Cr removal and the treatment of tannery effluent using water hyacinth resulted in 32.42% reduction of Cr after 7 days and 54.72% after 15 days. The present results revealed that water hyacinth had the strong capability of absorbing Cr. On the other hand, the reduction rates after 15 days for sedimentation were: 54.23% for BOD, 30.21% for TDS, 22.28% for EC and 14.37% for Cr. After comparing the two treatment processes, it was found that the reduction rate by phytoremediation process was much higher than that of sedimentation process. This result reflected the high efficiency of water hyacinth to reduce pollutant especially Cr from tannery effluent as eco-friendly sustainable technology.Res. Agric., Livest. Fish.4(3): 151-156, December 2017